Friday

April 25, 2014

April 25, 2014

Posted by **max** on Monday, January 7, 2013 at 9:22pm.

- math -
**Reiny**, Monday, January 7, 2013 at 10:15pm(1 1/4 x - 5 1/6) - (5/8 x + 1 1/3)

in better form

((5/4)x + 31/6 - ((5/8)x + 4/3)

= (10/8)x - (5/8)x + 31/6 - 8/6

= (5/8)x + 23/6

**Related Questions**

math, beginning algebra - how do you solve this i've tried many ways and i ...

algbra - i was wondering what did i do wrong in this 10. Divide (3x – 2)(x - 4...

math,algebra - how do you solve this problem 3 and 1/3 subtracted by 1 and 2/3? ...

math - Can someone help me finish this problem I am stuck! 5/4x+1/8x=11/8+x 10/...

Math - I have a problem..... -4(2x-3)=-8x+5 I understand first you distribute ...

Math - f(x+1)=8x^2+x-3 f(-x)=8x^2+x-3 work: #1 8(x+1)(x+1)+x-3 then FOIL 8(x^2+x...

Math - Solve each equation by completing the square. -36x=8x^2+28 -8x^2-3x=-5 5x...

Math - Solve each equation by completing the square. -36x=8x^2+28 -8x^2-3x=-5 ...

math(check my answers) - SOLVE THE FOLLOWING EQAUTION BY COMPLETING THE SQUARE: ...

Algebra - Which equation could be used to find the dimensions of a room that has...